1999
DOI: 10.3758/bf03201211
|View full text |Cite
|
Sign up to set email alerts
|

The importance of semantic similarity to the irrelevant speech effect

Abstract: Irrelevant speech disrupts immediate recall of a short sequence of items. Salame and Baddeley (1982) found a very small and nonsignificant increase in the irrelevant speech effect when the speech comprised items semantically identical to the to-be-remembered items, leading subsequent researchers to conclude that semantic similarity plays no role in the irrelevant speech effect. Experiment 1 showed that strong free associates of the to-be-remembered items disrupted serial recall to a greater extent than words t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
91
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 28 publications
7
91
1
Order By: Relevance
“…First, they demonstrate that with different types of recall test (free recall) and auditory distracter (semantically related), the OSPAN measure still fails to distinguish between individuals who suffer from high or low levels of irrelevant sound interference when the dependent measure is the number of correct recalls. Second, the results are the first replication of Neely and LeCompte's (1999) demonstration of semantically mediated irrelevant speech effects in free recall, and they extend the findings of those authors in also showing a reliable effect of intrusion by irrelevant speech items into the free recall protocols in relatedspeech conditions. Third, and most importantly, the results demonstrate that intrusions from semantically related irrelevant speech occur more frequently among low-than high-OSPAN participants, providing a conceptual replication previously lacking for the results of Conway et al (2001) and also suggesting a means by which the results of this experimental series can be reconciled with the data from Conway et al's dichotic listening task.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, they demonstrate that with different types of recall test (free recall) and auditory distracter (semantically related), the OSPAN measure still fails to distinguish between individuals who suffer from high or low levels of irrelevant sound interference when the dependent measure is the number of correct recalls. Second, the results are the first replication of Neely and LeCompte's (1999) demonstration of semantically mediated irrelevant speech effects in free recall, and they extend the findings of those authors in also showing a reliable effect of intrusion by irrelevant speech items into the free recall protocols in relatedspeech conditions. Third, and most importantly, the results demonstrate that intrusions from semantically related irrelevant speech occur more frequently among low-than high-OSPAN participants, providing a conceptual replication previously lacking for the results of Conway et al (2001) and also suggesting a means by which the results of this experimental series can be reconciled with the data from Conway et al's dichotic listening task.…”
Section: Discussionsupporting
confidence: 83%
“…If OSPAN reflects the ability to reject stimuli at a different stage in processing than that represented by the irrelevant sound distracters, possibly during semantic analysis, high-span participants could exclude the highly meaningful stimulus in Conway et al's cocktail party paradigm quite efficiently but this capability would be of no use in attempting to ignore the rather less meaningful stimuli (nonwords and tones) of Experiments 2 to 3. In accordance, Experiment 4 used a modification of Neely and LeCompte's (1999) free recall procedure to determine whether OSPAN could account for the effects of irrelevant speech at the semantic level.…”
Section: Discussionmentioning
confidence: 99%
“…The present results also add to the growing body of evidence of an attentional involvement in the irrelevant-sound effect (Buchner & Erdfelder, 2005;Buchner et al, 2006;Buchner et al, 2004;Elliott, 2002;Lange, 2005;Neely & LeCompte, 1999). Like those results, the finding that the irrelevant-sound effect is modulated by the proximity of the auditory distractors to the direction of attention can be readily explained within the embedded-processes model of working memory (Cowan, 1995(Cowan, , 1999) and the feature model (Nairne, 1990;Neath, 2000), because both models comprise an attentional component.…”
Section: Discussionsupporting
confidence: 59%
“…Assuming that attentional control improves during this time period, Elliott suggested that this was evidence of an involvement of attention in the genesis of the irrelevant-sound effect. Neely and LeCompte (1999) showed that a strong semantic association between visual targets and auditory distractors may play a role for serial recall performance (but see Buchner, Irmen, & Erdfelder, 1996;LeCompte & Shaibe, 1997, for conflicting results). Buchner and Erdfelder (2005) showed that the frequency of auditory distractor words may affect the serial recall of Procedure.…”
mentioning
confidence: 99%
“…In addition, this account seems a bit stretched with respect to Experiment 2. There, the prime never occurred among the three test words, and it seems doubtful that searching for and finding a semantically related word really would facilitate maintaining the memorized item; one might even expect similar materials to produce strong interference (see, e.g., Neely & LeCompte, 1999).…”
Section: Discussionmentioning
confidence: 99%